Nepali IT Employees’ Perception towards Telecommuting: A Qualitative Study - Bijendra Rajbanshi (Indonesian Journal of Social Science Research, 2022)
This research tries to explore the perception of Nepali IT employees towards telecommuting in a qualitative method. It tries to dig into the opportunities that the Nepali context offers for the adoption of telecommuting concept and identify the potential pitfalls. The individual interview method was chosen for the data collection. The semi-structured guideline was followed. Convenience sampling was used. Four employees working in IT companies inside the Kathmandu Valley were interviewed. 100 % of the participants reported that this concept is advantageous in the case of Nepal. Flexibility, freedom in doing work, increases in productivity, work-life balance, and cost-effectiveness were found to be perceived advantages of telecommuting in the context of Nepal. Worsening of communication and lack of infrastructure, disturbances in the house are perceived disadvantages. Furthermore, the inclusion of wide diversity of workforce is the prominent opportunity of telecommuting while the implementation part is the main hurdle as it is a new concept in the case of Nepal.